Evaluation, Remedy of Waste, Lean Hospital Method, Process of Inpatient Pharmacy Services in Hospital - Yunilah Sukmadryani; Wiwin Herdwiani; Tri Wijayanti (Syntax Corporation Indonesia, 2023)
Each installation in the hospital must continue to evaluate, improvement, and develop, including the pharmacy installation. Pharmacy installations as one of the medical support services in hospitals are required to improve the quality of their services on an ongoing basis. This study aims to see, the root of the problem, and provide evaluation and improvement for the reading of critical waste in the inpatient pharmacy service process of Kabupaten Karanganyar Hospital. This study uses a non-experimental research design and was descriptive qualitative in nature. Data techniques in qualitative and quantitative research. The value of patient data was obtained from distributing questionnaires. The pharmaceutical service process was obtained from observation and document review, then mapping in the form of value stream mapping. The determination of waste was obtained from distributing questionnaires and in-depth interviews with the 5 why method. The results of the reasearch show critical waste on inpatient service in pharmacy installation is waste defect and waste waiting. The root cause of critical waste is the prescription of drugs by doctors outside the formulary and the root cause of waiting for waste is a prescription from the hospital admission at the same time. The proposed improvement for the cause of critical waste is Monitoring and evaluating the implementation of the formularium on an going basis, provide special software to enter patient data, and implement the use of electronic prescribing to shorten the service process time.